Comparison between wet and dry methods of starch extraction from fresh sago pith - Jenefer, James Moinsol (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Melroxylon sagu or commonly known as 'sago palm' is the most promising starch-producing crop in Malaysia whereby many products can be derived from its starch in both food and non- food industries worldwide. This unique palm which can strive in peat soils, with less monitoring needed is reported to be able to produce starch approximately 20 kgllog. In this project, fresh sago pith samples were obtained from Samarahan whereby it was subjected to starch extraction by dry and commercial wet extraction method. The dry process was conducted strictly without the use of water in which the fresh sago pith was sliced into thin pieces, oven dried at 60oC, grounded and sieved to produce fine sago powder. In the wet method, the sago filtrate and its residue (sago hampas) were hydrolyzed separately whereby the sago hampas was oven dried at 600C prior to hydrolysis. In the hydrolysis of sago starch, Termamyl- 120L was used in liquefaction whereas AMGfurther digest the liquid starch in saccharification process. The starch content and recovery in the dry method was 207.1 giL and 20.7% whereas in the wet method sago filtrate contain 147.1 giL starch with 14.7% recovery whereby its residue shows lower starch content of 92.1 giL with only 9.2% recovery. The glucose recovery for starch from the dry method was 88.9% whereas from starch in the wet method was 69.1% in the sago filtrate and 59.1% in the sago hampas. Therefore, dry method has proven to be more effective compared to wet extraction in extracting starch from fresh sago pith with higher starch content (207.1 giL) and recovery (20.7%) as well as producing high glucose recovery (88.9%).